Parenthood and stress of caring for infants in different circumstances in Finland. Issue 6 (25th April 2020) - Martinviita-Hietala, Mariia; Joskitt, Leena; Ebeling, Hanna; Yliherva, Anneli; Moilanen, Irma
ABSTRACT: Risk factors for parenthood, early interaction and parents' perception of their 1-year-old child were examined in relation to the demographic and pregnancy-related background factors and to the further training for public health care nurses (PHCNs), according to European Early Promotion Project (EEPP). The short version of the Parenting Stress Index questionnaire was presented to parents of infants ( n  = 632) during their routine visits to health care centres. About half of the PHCNs were trained according to the EEPP service (intervention group). Non-working status and unwantedness of pregnancy were identified as risk factors for parental distress. Single parenthood was a risk factor for maternal distress. Non-working status, low education, unwanted pregnancy and living in rural areas contributed to the risk of difficulties in father–child interaction. Non-working fathers experienced most difficulties in accepting the child's behaviour. EEPP Intervention associated with fathers' views of their children in reconstituted families. Single mothers and mothers of unwanted children need special support for adapting to motherhood.